Inequity of antenatal influenza and pertussis vaccine coverage in Australia: the Links2HealthierBubs record linkage cohort study, 2012-2017 - Lisa McHugh; Annette K Regan; Mohinder Sarna; Hannah C Moore; Paul Van Buynder; Gavin Pereira; Christopher C Blyth; Karin Lust; Ross M Andrews; Kristy Crooks; Peter Massey; Michael J Binks (BMC, 2023)
Abstract Background Pregnancy and early infancy are increased risk periods for severe adverse effects of respiratory infections. Aboriginal and/or Torres Strait Islander (respectfully referred to as First Nations) women and children in Australia bear a disproportionately higher burden of respiratory diseases compared to non-Indigenous women and infants. Influenza vaccines and whooping cough (pertussis) vaccines are recommended and free in every Australian pregnancy to combat these infections. We aimed to assess the equity of influenza and/or pertussis vaccination in pregnancy for three priority groups in Australia: First Nations women; women from culturally and linguistically diverse (CALD) backgrounds; and women living in remote areas or socio-economic disadvantage. Methods We conducted individual record linkage of Perinatal Data Collections with immunisation registers/databases between 2012 and 2017. Analysis included generalised linear mixed model, log-binomial regression with a random intercept for the unique maternal identifier to account for clustering, presented as prevalence ratios (PR) and 95% compatibility intervals (95%CI). Results There were 445,590 individual women in the final cohort. Compared with other Australian women (n = 322,848), First Nations women (n = 29,181) were less likely to have received both recommended antenatal vaccines (PR 0.69, 95% CI 0.67-0.71) whereas women from CALD backgrounds (n = 93,561) were more likely to have (PR 1.16, 95% CI 1.10-1.13). Women living in remote areas were less likely to have received both vaccines (PR 0.75, 95% CI 0.72-0.78), and women living in the highest areas of advantage were more likely to have received both vaccines (PR 1.44, 95% CI 1.40-1.48). Conclusions Compared to other groups, First Nations Australian families, those living in remote areas and/or families from lower socio-economic backgrounds did not receive recommended vaccinations during pregnancy that are the benchmark of equitable healthcare. Addressing these barriers must remain a core priority for Australian health care systems and vaccine providers. An extension of this cohort is necessary to reassess these study findings.